Internet of Things (IoT) Arduino-Based Classroom Monitoring Utilizes Temperature Sensors And CO2 Sensors - Tri Suratno; Edi Saputra; Zainil Abidin; Daniel Arsa; Norman Syarief (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2022)
Comfort room temperature is determined by indoor air quality, such as temperature and CO2 gas. This study aims to determine the comfort of a class by reviewing the number of students, CO2 gas, and temperature in an Arduino-based classroom using an automatic IoT system with a Completely Randomized Design (CRD) method. Research proves that there is a significant effect between the number of students on the concentration of CO2, but it does not directly affect the air temperature in the room. The lecture hall is still relatively safe but not ideal and requires a temperature reduction of -7oC.